Measurement of f1(1285) production in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Physics letters, 2025)
This study presents the first measurement of the f1(1285) resonance using the ALICE detector in inelastic proton-proton collisions at a center-of-mass energy of 13 TeV. The resonance is reconstructed at midrapidity (|y|< 0.5) through the hadronic decay channel f1(1285)→KS0K±π∓. Key measurements include the determination of its mass, transverse-momentum integrated yield, and average transverse momentum. Additionally, the ratio of the transverse-momentum integrated yield of f1(1285) to pion is compared with calculations from the canonical statistical hadronization model. The model calculation, assuming a zero total strangeness content for f1(1285), reproduces the data within 1σ deviation, shedding light on the quark composition of f1(1285).